EMANCIPATION THROUGH CRITIQUE: Critical Islam and the Ethical Question - Belhaj, Abdessamad (Islamijah: Journal of Islamic Social Sciences, 2024)
Through the works of Ebrahim Moosa (South Africa, India, and the United States) and al-Ṭāhir Amīn (Tunisia), this article examines how critical Islam might be used to address the problems facing the Muslim world. It contends that the ethical thesis—that emancipation begins with the formation of a Muslim autonomous self via a reexamination of the Muslim heritage—is highlighted by critical Islam.  It is demonstrated that critical Islam is open to modernity and critical of Western imperialism, emphasizes the individual's religious experience, historizes the understanding of religious literature, and deviates from tradition. However, it prioritizes deconstruction above novel theological concepts, ignores spirituality, and has little effect on the majority of theologians.